(LACK OF) LEGAL REGULATION OF MULTIMODAL CARRIAGE IN THE REPUBLIC OF LITHUANIA - Mitkevičius, Vilius (Teisė, 2017)
Author analyses legal regulation of multimodal carriage in the Republic of Lithuania and the law applicable to the multimodal contract for the carriage of goods. The article contains suggestions how to improve the legal regulation in Lithuania as well.